ANALISIS PREDIKSI KEBANGKRUTAN (FINANCIAL DISTRESS) DENGAN PERBANDINGAN MODEL ALTMAN, ZMIJEWSKI DAN GROVER - M. Agus Sudrajat; Eka Wijayanti (Universitas PGRI Madiun, 2019)
The purpose of this study is to analyze bankruptcy predictions (Financial Distress) with a Comparison of the Altman Model (Z-Score), Zmijewski (X-Score) and Grover (G-Score) (Empirical Study in Manufacturing Companies in the Basic Industrial and Chemical Sector Sectors registered in IDX 2015-2018). This study uses non-parametric statistical data analysis with Kruskal Wallis different test. The research sample is 37 companies manufacturing basic and chemical industrial sectors which are listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. The data used in this study are secondary data derived from the company's financial statements. The research sample was selected by purposive sampling technique with predetermined criteria. Hypothesis test results showed there are differences in predictions between the Altman model (Z-Score), Zmijewski (X-Score) and Grover (G-Score) in predicting bankruptcy (financial distress) of manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange period 2015-2018. The Grover (G-Score) model is the most accurate prediction model with an accuracy level of 85.14%. While the Altman model (Z-Score) has an accuracy rate of 77.70% and the Zmijewski model (X-Score) of 79.73%.Keywords: Financial Distress, Altman Model, Zmijewski Model and Grover Model.